New records of decapod crustaceans from Kuwait (Malacostraca: Decapoda) - Al-Kandari, M; Anker, A; Hussain, S; Al-Yassen, S; Sattari, Z (Magnolia Press, 2020)
Seventeen species of shrimp-like decapod crustaceans (infraorders Caridea, Axiidea and Gebiidea) and two species of porcelain crabs (infraorder Anomura) are recorded for the first time from Kuwait, some of them also representing new records for the Arabian Gulf. The new records from Kuwait are: (1) Alpheus edamensis De Man, 1888; (2) Alpheus edwardsii (Audouin, 1826); (3) Alpheus macrodactylus Ortmann, 1890; (4) Alpheus maindroni Coutière, 1898; (5) Arete indicus Coutière, 1903; (6) Athanas parvus De Man, 1910; (7) Synalpheus gracilirostris De Man, 1910 [all Alpheidae]; (8) Latreutes mucronatus (Stimpson, 1860) [Hippolytidae]; (9) Thor paschalis (Heller, 1862) [Thoridae] (10) Periclimenella pettithouarsii (Audouin, 1826); (11) Anchistus custos (Forskål, 1775); (12) Urocaridella pulchella Yokes & Galil, 2006 [all Palaemonidae]; (13) Chlorocurtis jactans (Nobili, 1904) [Chlorotocellidae]; (14) Upogebia carinicauda (Stimpson, 1860); (15) Upogebia octoceras Nobili, 1904 [Upogebiidae]; (16) Balsscallichirus masoomi (Tirmizi, 1970), (17) Michaelcallianassa indica Sakai, 2002 [Callianassidae]; (18) Raphidopus persicus Ng, Safaie & Naser, 2012 and Polyonyx obesulus Miers, 1884 [Porcellanidae]. Most of these taxa have been previously recorded from other parts of the Arabian Gulf, mainly from the coasts of Iran and the United Arab Emirates, except for A. maindroni and U. pulchella, which are recorded from the Arabian Gulf for the first time. Most species are shown in colour photographs, some for the first time. In addition, the presence of Synalpheus quinquedens Tattersall, 1921 (Alpheidae), previously known from Kuwait based only on a questionable record in a popular field guide, is confirmed based on a single collected and preserved specimen.